2008
DOI: 10.1073/pnas.0709336105
|View full text |Cite
|
Sign up to set email alerts
|

The PINK1/Parkin pathway regulates mitochondrial morphology

Abstract: Loss-of-function mutations in the PTEN-induced kinase 1 (PINK1) or parkin genes, which encode a mitochondrially localized serine/ threonine kinase and a ubiquitin-protein ligase, respectively, result in recessive familial forms of Parkinsonism. Genetic studies in Drosophila indicate that PINK1 acts upstream of Parkin in a common pathway that influences mitochondrial integrity in a subset of tissues, including flight muscle and dopaminergic neurons. The mechanism by which PINK1 and Parkin influence mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
674
4
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 787 publications
(717 citation statements)
references
References 61 publications
34
674
4
5
Order By: Relevance
“…Moreover, further genetic analyses using mitochondrial fusionfission regulators demonstrated that PINK1 and parkin mutant phenotypes are successfully rescued by the overexpression of Drp1, a dynamin-related GTPase that promotes mitochondrial fission, or the downeregulation of Opa1 or Marf, which are other dynamin-related GTPases that induce mitochondrial fusion (Deng et al, 2008;Park et al, 2009;Poole et al, 2008;Yang et al, 2008). These findings suggest that PINK1 and Parkin balance mitochondrial dynamics by promoting mitochondrial fission to properly maintain mitochondrial function.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 87%
“…Moreover, further genetic analyses using mitochondrial fusionfission regulators demonstrated that PINK1 and parkin mutant phenotypes are successfully rescued by the overexpression of Drp1, a dynamin-related GTPase that promotes mitochondrial fission, or the downeregulation of Opa1 or Marf, which are other dynamin-related GTPases that induce mitochondrial fusion (Deng et al, 2008;Park et al, 2009;Poole et al, 2008;Yang et al, 2008). These findings suggest that PINK1 and Parkin balance mitochondrial dynamics by promoting mitochondrial fission to properly maintain mitochondrial function.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 87%
“…A genetic interaction between the PINK1/Parkin pathway and the fission/fusion machinery was discovered in flies where overexpression of Drp1 led to suppression of mitochondrial defects in PINK1 and Parkin mutants. 66 Although similar studies in mammalian systems have produced contradictory results, 64,67 the findings in the fly indicate that PINK1 and Parkin promote fission. Consistent with this conclusion, mammalian and fly studies indicate that upon mitochondrial depolarization, Parkin translocates to mitochondria and causes polyubiquitination of Mitofusin, targeting it for removal from the mitochondrial membrane by the p97 AAA-ATPase and subsequent proteosomal degradation [55][56][57] ( Figure 4bi).…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 99%
“…Therefore, defective mitophagy due to a lack of parkin recruitment to impaired mitochondria by PINK1 causes the accumulation of dysfunctional mitochondria and a subsequent enhanced ROS levels and proapoptotic proteins [257]. In addition, overexpression of PINK1 promotes mitochondrial fission, while inhibition of the protein causes an excessive fusion [258,259]. Fibroblasts from PD patients carrying homozygous PINK1 mutations had truncated mitochondria networks compared to control fibroblasts, when cultured in medium with low glucose, or in the presence of galactose to favor mitochondrial energy metabolism over glycolysis [243,260].…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 99%